Musée de Bruxelles. D. Teniers 1610-1694. Le médecin de village (02)... - Teniers | David | II (Wikimedia Commons)
Carte postale ancienne issue de Wikimedia Commons. Titre: Musée de Bruxelles. D. Teniers 1610-1694. Le médecin de village (02), GP019316. Title Musée de Bruxelles. D. Teniers 1610-1694. Le médecin de village [02] Contributor Teniers, David, II (Flemish painter and etcher, 1610-1690) (author original work) Date [date de publication inconnu] Publisher Bruxelles: Nels Uniform title Bruxelles-Brussel. Beelden en objecten. Koninklijke Musea voor Schone Kunsten van België Series Belgique. Région de Bruxelles-Capitale. Cartes postales Belgium. Brussels-Capital Region. Postcards België. Brussels Hoofdstedelijk Gewest. Prentkaarten Genre Post cards Extent 1 kaart / postcard Graphic Black-and-white Language French Additional info General note: Museum van Brussel. D. Teniers 1610-1690. De Dorpsheelmeester General note: Titelgegevens ontleend aan prentkaart Source Library Catalog Source ID lbsn9992295051401471
Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; Patrimoine; Histoire Locale; Wikimedia Commons